Influence of Service Quality on Inpatient Satisfaction at Karisma Cimareme Hospital - Leni Hartati; Ginanjar Wira Saputra; Fajar Try Noegraha (Program Studi Administrasi Bisnis, 2023)
This study aims to examine the effect of the quality of hospital services on the satisfaction of hospitalized patients in karisma cimareme hospitals. The method used is a descriptive method with a quantitative approach, while the data collection technique is carried out by spreading questionnaires to a number of respondents of hospitalization patients Karisma Cimareme Hospital. Based on the correlation coefficient between variable X (Quality of Service), and variable Y (Patient Satisfaction) of 0.667 proved there is a positive and significant relationship between variable X (Quality of Service) and variable Y (Patient Satisfaction). Meanwhile, based on the coefficient of determination (KD), it is known that the achievement of variable X's ability affects variable Y which is 44.49% while the remaining 55.51% is influenced by other variables not studied in this study. Based on the results of research can be put forward, variables on the quality of hospital services and patient satisfaction variables are good. Some of the suggestions that researchers conveyed were to cultivate 5S smiles, greetings, greetings, manners and manners, so that hospital patients feel satisfied and comfortable getting services from Karisma Cimareme Hospital.